Ambiguity aversion as a reason to choose tournaments - Christian Kellner; Gerhard Riener (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We test the implications of ambiguity aversion in a principal-agent problem with multiple agents. When output distributions are uncertain, models of ambiguity aversion suggest that tournaments may become more attractive than independent wage contracts, in contrast to the case where output distributions are known. We do so by presenting agents with a choice between tournaments and independent contracts, which are designed in a way that under uncertainty about output distribution (that is, under ambiguity), ambiguity averse agents should typically prefer tournaments, while ambiguity neutral agents prefer independent contracts, independent of their degree of risk aversion. This is the case, because the tournament removes all ambiguity about the equilibrium wages. We compare the share of participants who choose the tournament under ambiguity with the share of participants choosing the tournament in a control treatment, where output distributions are know. As the theory predicts, we find indeed that under ambiguity the share of agents who choose the tournaments is higher than in the case of known output distributions.
Keywords: D01; D03; D81; M55; 330; ambiguity aversion; tournaments; Ellsberg urn; contract design; Prinzipal-Agent-Theorie; Risikoaversion; Extensives Spiel; Arbeitsvertrag; Test